"\\frac {dy}{dx}+\\frac {x}{1-x^2}y=x\\sqrt{y} , y(0)=1"
Trivial solution "y=0", but there is "y(0)=1" . That's why we can't take it.
Further we consider that "y\\neq0."
"y'+\\frac{x}{1-x^2}y=x\\sqrt{y}\\\\\n\\frac{y'}{\\sqrt{y}}+\\frac{x\\sqrt{y}}{1-x^2}=x"
Let "\\sqrt{y}=z", then "z'=(\\sqrt{y})'=\\frac{y'}{2\\sqrt{y}}" and "\\frac{y'}{\\sqrt{y}}=2z'"
"2z'+\\frac{xz}{1-x^2}=x"
Let "z=uv", then "z'=u'v+uv'"
"2u'v+2uv'+\\frac{xuv}{1-x^2}=x\\\\\n2u'v+u(2v'+\\frac{xv}{1-x^2})=x" (1)
"2v'+\\frac{xv}{1-x^2}=0\\\\\n2v'=\\frac{xv}{x^2-1}\\\\\n2\\frac{dv}{dx}=\\frac{xv}{x^2-1}\\\\\n2\\frac{dv}{v}=\\frac{xdx}{x^2-1}\\\\\n2\\int\\frac{dv}{v}=\\int\\frac{xdx}{x^2-1}\\\\\n2log(|v|)=1\/2log(|x^2-1|)\\\\\nv=\\sqrt[4]{|x^2-1|}"
Now (1) is "2u'\\sqrt[4]{|x^2-1|}=x"
"2\\frac{du}{dv}=\\frac{x}{\\sqrt[4]{|x^2-1|}}\\\\\n2du=\\frac{xdx}{\\sqrt[4]{|x^2-1|}}\\\\\n2\\int du=\\int \\frac{xdx}{\\sqrt[4]{|x^2-1|}}\\\\\n2\\int du=\\frac{1}{2}\\int \\frac{dx^2}{\\sqrt[4]{|x^2-1|}}\\\\\nu=\\frac{1}{3}\\sqrt[4]{|x^2-1|}^3+C"
Finally
"z=uv=\\sqrt[4]{|x^2-1|}\\frac{1}{3}(\\sqrt[4]{|x^2-1|}^3+C)=\\frac{1}{3}(|x^2-1|)+C\\sqrt[4]{|x^2-1|}"
"\\sqrt{y}=\\frac{1}{3}(|x^2-1|)+C\\sqrt[4]{|x^2-1|}\\\\\ny=(\\frac{1}{3}(|x^2-1|)+C\\sqrt[4]{|x^2-1|})^2"
"y(0)=1, \\implies \\\\\n1=(\\frac{1}{3}|-1|+C\\sqrt[4]{|-1|})^2\\\\\n1=(\\frac{1}{3}+C)^2"
"C=\\frac{2}{3}" or "C=-\\frac{4}{3}"
"y=(\\frac{1}{3}(|x^2-1|)+\\frac{2}{3}\\sqrt[4]{|x^2-1|})^2" or
"y=(\\frac{1}{3}(|x^2-1|)-\\frac{4}{3}\\sqrt[4]{|x^2-1|})^2"
Comments
Leave a comment